An investigation of effect of stepped chutes with end sill on aeration performance - Emiroglu, ME; Baylar, A (Canadian Assoc Water Quality, 2003)
Dissolved oxygen is essential to healthy streams and lakes. The dissolved oxygen level is an indication of how polluted the water is and how well the water can support aquatic plant and animal life. A higher dissolved oxygen level indicates better water quality. There is a significant oxygen transfer associated with most hydraulic structures because the air entrained into the flow is split into small bubbles, which greatly increases the surface area for transfer. Stepped chutes are a particular instance of this, and the aeration efficiency of such structures has not been studied in the laboratory and field. In this paper, the aeration performance of the stepped chutes with and without end sill was investigated in a large laboratory stepped chute. An empirical correlation predicting the oxygen transfer efficiency was developed for stepped chutes. The results indicated that 1/h and s/h had a significant effect on the aeration efficiency of stepped chutes.
Keywords: oxygen transfer; dissolved oxygen; aeration efficiency; stepped chute; sill